Inherited thrombophilia polymorphisms and pregnancy outcomes in nulliparous women - Said, J.; Higgins, J.; Moses, Eric; Walker, S.; Borg, A.; Monagle, P.; Brennecke, S. (Lippincott Williams & Wilkins, 2010)
Objective: To estimate the association between five commonly inherited thrombophilia polymorphisms and adverse pregnancy outcomes in women who had no prior history of adverse pregnancy outcomes or personal or family history of venous thromboembolism. Methods: Healthy nulliparous women (n=2,034) were recruited to this prospective cohort study before 22 weeks of gestation. Genotyping for factor V Leiden, prothrombin gene mutation, methylenetetrahydrofolate reductase enzyme (MTHFR) C677T, MTHFR A1298C, and thrombomodulin polymorphism was performed. Clinicians caring for women were blinded to the results of thrombophilia tests. The primary composite outcome was the development of severe preeclampsia, fetal growth restriction, placental abruption, stillbirth, or neonatal death. Results: Complete molecular Results and pregnancy outcome data were available in 1,707 women. These complications were experienced by 136 women (8.0%). Multivariable logistic regression demonstrated two statistically significant findings. Women who carried the prothrombin gene mutation had an odds ratio of 3.58 (95% confidence interval [CI] 1.20-10.61, P=.02) for the development of the composite primary outcome. Homozygous carriers of the MTHFR 1298 polymorphism had an odds ratio of 0.26 (95% CI 0.08-0.86, P=.03). None of the other polymorphisms studied showed a significant association with the development of the primary outcome in this cohort of women. CONCLUSION: Prothrombin gene mutation confers an increased risk for the development of adverse pregnancy outcomes in otherwise asymptomatic, nulliparous women, whereas homozygosity for MTHFR 1298 may protect against these complications. The majority of asymptomatic women who carry an inherited thrombophilia polymorphism have a successful pregnancy outcome. © 2009 by The American College of Obstetricians and Gynecologists. Published by Lippincott Williams & Wilkins.